The Influence of Pilates Exercise on Women`s Anthrophometry Indices, Core Muscle Performance and Heart Rate Changes during the Session (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Pilates exercises are used in fitness and in some forms of rehabilitation programs (Di Lorenzo, 2011). Pilates focuses on core body exercise and activation of transversus abdominis muscle (TrA), multifidus and pelvic floor muscles can also be used as an exercise programme controlling body mass and blood pressure. Little is known about the Pilates exercise intensity and heart rate changes during the practice session.The aim of the current research was to study the impact of Pilates exercise on women’s body weight, core muscle performance and to evaluate heart rate changes during the practice session.Research methods included anthropometry measurements, heart rate and core muscle performance measures.Research results. In the period of 8-week Pilates training we found that it had a significant impact on women’s fat body mass and static core muscle endurance. Slightly decreasing tendency was found in BMI, but there were no statistically different changes between the results at the beginning and after 8-week training period. Measuring HR changes during the Pilates session we found that moderate HR was 98.2 (4.7) beats/min and maximum HR was 131.4 (7.2) beats/min. Maximum HR took approximately 10% and moderate HR – 90% of training period time. Discussion  and  conclusions. We  found  that  8-week  Pilates  training  period  had  a  positive  influence  on  the participants’ core muscle performance, fat body mass and minor BMI reduction. As a result, Pilates exercises could be used for the prevention of low back pain and to reduce obesity. Slight HR changes during the session indicate that Pilates exercises may have implications for the rehabilitation of individuals who have high blood pressure and cannot go in for high intensity physical activity.Keywords: BMI, heart rate, Pilates training, static endurance of core muscles